Government Policy in Efforts to Merge State-Owned Enterprises - Sheraton, Anelis; Wirawan, Bryan Chandra; Siregar, Pelita Roliana; Silvia, Silvia; Lestarie, Yurie; Manuela, Zevanka; Sitorus, Rolib (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research conducted aims to determine the factors underlying the need for the merger of State-Owned Enterprises and the legal basis and regulations that govern and influence the process of merging State-Owned Enterprises, and to determine the strategy and approach to the merger of State-Owned Enterprises and the implementation of company merger policies, as well as their impact on the economy and industry. The method used is qualitative and normative legal research, with a focus on regulations such as Law No. 19 of 2003 concerning State-Owned Enterprises and PP No. 43 of 2005. The expected results are that through the SOE merger strategy includes acquisition, merger, and consolidation, with a legal, economic, management, and social approach. The merger also considers the social impact on employees and maintains transparent communication. ⁠The positive impacts of the policy include reducing operational costs, increasing efficiency, and increasing contributions to food security, state revenue, and production capacity in the construction sector. The state-owned banking holding also showed a significant increase in market capitalization, increasing competitiveness at the global level. ⁠The merger policy also faces internal challenges, such as employee resistance and obstacles to organizational cultural integration, as well as external challenges from global economic fluctuations and changes in commodity prices. Solutions that can be taken are effective communication, employee redeployment, and the impact of the policy is continuously evaluated.